A Flourishing Economist: A Review Essay on Edmund Phelps's Mass Flourishing: How Grassroots Innovation Created Jobs, Challenge, and Change - Mokyr, Joel (Journal of Economic Literature, 2014)
In his recent Mass Flourishings, Edmund Phelps makes a strong and eloquent plea for a more dynamic economy, which he sees not only as a key for economic performance, but also as necessary for what he calls “the good life.” This review essay evaluates those claims in the light of economic history. (JEL E02, N00, O10, O30, P16)